NADPH oxidases in the arbuscular mycorrhizal symbiosis. (2nd April 2016) - Belmondo, Simone; Calcagno, Cristina; Genre, Andrea; Puppo, Alain; Pauly, Nicolas; Lanfranco, Luisa
ABSTRACT: Plant NADPH oxidases are the major source of reactive oxygen species (ROS) that plays key roles as both signal and stressor in several plant processes, including defense responses against pathogens. ROS accumulation in root cells during arbuscular mycorrhiza (AM) development has raised the interest in understanding how ROS-mediated defense programs are modulated during the establishment of this mutualistic interaction. We have recently analyzed the expression pattern of 5 NADPH oxidase (also called RBOH) encoding genes in Medicago truncatula, showing that only one of them ( MtRbohE ) is specifically upregulated in arbuscule-containing cells. In line with this result, RNAi silencing of MtRbohE generated a strong alteration in root colonization, with a significant reduction in the number of arbusculated cells. On this basis, we propose that MtRBOHE-mediated ROS production plays a crucial role in the intracellular accommodation of arbuscules.